PENGARUH FAKTOR SPESIFIK DAN FAKTOR EKSTERNAL BANK TERHADAP PROFITABILITAS PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BEI - Nabila Putri Lisandrina; Susy Muchtar (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
This study aims to examine the effect of bank-specific factors on banking profitability. The samples used in this study were 33 conventional banks listed on the Indonesia Stock Exchange during 2017-2021. The sampling technique used was purposive sampling and the analytical method used in this study was panel data regression. The independent variables in this study consist of bank size, loan ratio, deposit ratio, capital ratio, and inflation, while the dependent variable is banking profitability which includes return on asset and return on equity. The panel data regression results show that bank size has a significant positive effect on return on asset, but has no effect on return on equity. The loan ratio, deposit ratio, and capital ratio have no effect on return on assets and return on equity. Inflation has a significant positive effect on return on asset, but does not affect return on assets. The results of this study are expected to be a reference for conventional banking in increasing its profitability as well as a reference for investors to consider the factors that affect bank profitability.